Enhancing Circular Economy Practices: Utilization of Livestock Manure for Biogas and Organic Fertilizer in Sangatta Selatan, East Kalimantan - Wijana, Susinggih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2025)
Cattle and sheep manure, raising environmental concerns. Through the Doktor Mengabdi (DM) initiative, a community service program was conducted at P4S Wisma Kemakmuran, South Sangatta, to implement sustainable waste management practices. Cattle manure was processed via anaerobic digestion to produce biogas and digestate, while sheep manure was composted into organic fertilizer. The program involved socialization, technology installation, field practice, and monitoring, ensuring active community participation. Biogas replaced fossil-based cooking gas, while compost improved soil fertility and livestock feed quality. These efforts reduced methane emissions, promoted renewable energy, and enhanced soil productivity. The program aligns with SDGs 7 (Affordable and Clean Energy), 11 (Sustainable Cities and Rural Communities), 12 (Responsible Consumption and Production), and 13 (Climate Action). Continued collaboration between Universitas Brawijaya and P4S Wisma Kemakmuran promises lasting environmental and economic benefits for the community.